(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
A progressive transformation of primordia is a common stage in the formation of lymph node sinuses regardless of their localization. A simultaneous formation of the regional reports from the sinus area of the gate through the slit-like rudiments of the intermediate sinuses seems to be the most probable combination.